2011
DOI: 10.1093/toxsci/kfr169
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Cancer-Related Pathways in Primary Hepatocytes Derived from DNA Repair-Deficient Xpa−/−p53+/− Mice upon Exposure to Benzo[a]pyrene

Abstract: The current method to predict carcinogenicity of chemicals or drugs is the chronic 2-year rodent bioassay, which has disadvantages in duration, animal use, and specificity. An attractive alternative is the DNA repair-deficient Xpa(-/-)p53(+/-) mouse model that is sensitive to both genotoxic and nongenotoxic carcinogens. A next step in alternative carcinogenicity testing is the development of reliable in vitro systems. We investigated the use of primary hepatocytes, isolated from wild-type (WT) and Xpa(-/-)p53(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Similarly, LIG4 upregulation has been associated with tobacco-related cancers and not BaP specifically, though BaP is a component of tobacco smoke (Wu et al, 2004). In addition, rodent studies of rats and mice found ortholog upregulation of UBE2B and PRDX5 as well as downregulation of DTD1 (Chen et al, 2001; van Kesteren et al, 2011). While none of the genes in Table 7, with the exception of select solute carriers previously discussed and VDAC1, have been conclusively linked to adverse outcomes in human cells and BaP exposure, they represent candidate susceptibility loci as they are related to carcinogenesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, LIG4 upregulation has been associated with tobacco-related cancers and not BaP specifically, though BaP is a component of tobacco smoke (Wu et al, 2004). In addition, rodent studies of rats and mice found ortholog upregulation of UBE2B and PRDX5 as well as downregulation of DTD1 (Chen et al, 2001; van Kesteren et al, 2011). While none of the genes in Table 7, with the exception of select solute carriers previously discussed and VDAC1, have been conclusively linked to adverse outcomes in human cells and BaP exposure, they represent candidate susceptibility loci as they are related to carcinogenesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For carcinogenicity, in vitro transcriptomics approaches are emerging (Guyton et al, 2009;Jacobs, 2009;van Kesteren et al, 2011;Vinken et al, 2008). These have been applied initially to genotoxic carcinogens , but the approach makes just as much sense for the non-genotoxic mechanisms, and there are early indications that genotoxic and non-genotoxic effects can be discriminated (Magkoufopoulou et al, 2011;Plant, 2008).…”
Section: Information-rich Single Testsmentioning
confidence: 99%
“…ITS are a consequence of REACH (van Leeuwen et al, 2007), which argues for the use of all available information and views use of the definitive animal experiment only as a last resort. However, the ITS suggested for reproductive toxicity (Fig.…”
Section: Integrated Testing Strategies (Its)mentioning
confidence: 99%
“…+/-mouse have been considered as a model for carcinogenicity screening (van Kesteren et al, 2011). As such, primary mouse hepatocytes seem a promising model for hepatic toxicity studies.…”
Section: P53mentioning
confidence: 99%